Comparison of Neutralizing Antibody Response to Type 1 Polio Virus on Healthy Infants Receiving either Oral Monovalen Polio Vaccine Type 1 or Oral Trivalen Polio Vaccine Given with Basic DTP/Hb Immunization - Hartati, Edim; Ismoedijanto, Ismoedijanto; Soegijanto, Soegeng (Indonesian Journal of Tropical and Infectious Disease, 2010)
In March 2005, there was outbreak of Polio-1 and expanded throughout Java and Sumatera island. Oral monovalent polio vaccinetype 1 (mOPV1) had succeeded in evereeming polio outbreak in Indonesia in 2005. This study aimed to compare neutralizing antibodyresponse to type 1 polio virus in healthy infants receiving either mOPV1 or oral trivalent Polio Vaccine (tOPV), given with other basicvaccination (DTP/HB). Randomized controlled singel blind clinical trial on healthy infants range age 42 to 80 days who had receivedfirst oral polio vaccine before 1 month of age. Trial group received mOPV1 and control group tOPV, each had 3 times of vaccination.Blood samples were taken three times (pre vaccination, post second and third vaccination) for measurement of neutralizing antibody topolio virus. Thirty subjects from mOPV1 group and 29 from tOPV group were analyzed. Post second vaccination, mOPV1 group (456)had more increase in geometric mean titer of neutralizing antibody than tOPV group (317) but not significant (p=0.514). Post thirdvaccination the level of neutralizing antibody titer was almost equal in both groups. Proportion of seroconversion to type 1 polio virusin mOPV1 group 53.9%, 57.7% and tOPV group 25.9%, 41.7% (on second and third evaluation respectively), both were statisticallyinsignificant. Antibody response measured by neutralizing antibody titer and proportion of seroconversion on antibody to type 1 poliovirus in healthy infants receiving mOPV1 vaccination was similar to they receiving tOPV.